What Is Justice? Perspectives of Victims-Survivors of Gender-Based Violence - Hester, Marianne (Violence against women, 2025)
This article explores “how do victims-survivors of gender-based violence (GBV) experience and perceive justice?” based on interviews with 251 victims-survivors with experience of different types of GBV and criminal, civil, and family justice systems. Victims-survivors were found to have multiple perceptions of justice, related to different points in their journey following abuse and regarding individual, community, and societal responses. Perceptions relate to accountability; fairness in outcome and process; protection from future harm; recognition; agency; empowerment; affective justice; reparation; and social transformation. Current understandings of justice in legislative and policy approaches reproduce the “justice gap” by failing to take account of how survivors themselves understand and demand justice.